Pelatihan dan Pembinaan Ekonomi Kreatif Pada BUMDes dan PKK Desa Kaladawa - M.Masrukhan; Stya Pramono (Jurnal Pelayanan Masyarakat, 2024)
BUMDES is a legal entity established by the village and/or together with the village to manage the business, utilize assets, develop investment and productivity, provide services, and/or provide other types of businesses for the greater welfare of the village community. So BUMDES itself is an economic activity that is managed independently by villagers. The Community Empowerment (PKM) activity carried out in Kaladawa Village is a creative economy training for youth organizations, aiming to apply a creative economy model so that youth youth organizations in Kaladawa village to create productive and creative people. This activity was held on Thursday, May 30, 2024, attended by 30 (thirty) participants consisting of the Village Head and his apparatus, Bumdes, Youth Organisation Youth and PKK women.